The functional significance of Diana monkey 'clear' calls - Uster, Dana; Zuberbühler, Klaus (My University, 2001)
In their natural West African rainforest habitat, Diana monkeys continuously produce high rates of a close-range clear-sounding call, but the function of this behaviour is unknown. In other primate species, close-range calls are typically given in socially relevant situations, for example, to gain access to grooming partners or food. Quite contrarily, we tested a number of hypotheses and found that Diana monkey 'clear' calls primarily function to avoid predation. Call rates were significantly elevated when predation threat was high, for instance when the visibility was poor, when the group spread was large, when the group was not associated with other monkey species. or after alarm calls. Call rates were not significantly elevated, however, in circumstances of high social competition, for instance when the group spread was small, during resting phases, while feeding oil clumped food sources, or when foraging in the periphery where inter-group encounters were more likely to occur. Calling was contagious in that calls typically elicited vocal responses from out-of-sight group members within a few seconds. Because of this, callers can effectively monitor a much larger area than is visually accessible to single individuals, suggesting that Diana monkey clear calls act as an essential element in a mutualistic system of co-ordinated vigilance.
Keywords: predation; vocal behaviour; Cercopithecus diana; watchman's song hypothesis; vigilance; alarm call; clear call